A randomised controlled feasibility trial of a clinical protocol to manage hypotension during major non‐cardiac surgery. (20th March 2022) - Wijeysundera, D. N.; Duncan, D.; Moreno Garijo, J.; Jerath, A.; Meineri, M.; Parotto, M.; Wąsowicz, M.; McCluskey, S. A.; ,
Summary: Intra‐operative hypotension is a risk factor for postoperative morbidity and mortality. Minimally invasive monitors that derive other haemodynamic parameters, such as stroke volume, may better inform the management of hypotension. As a prelude to a multicentre randomised controlled trial, we conducted a single‐centre feasibility trial of a protocol to treat hypotension as informed by minimally invasive haemodynamic monitoring during non‐cardiac surgery. We recruited adults aged ≥40 years with cardiovascular risk factors who underwent non‐cardiac surgery requiring invasive arterial pressure monitoring. Participants were randomly allocated to usual care, or a clinical protocol informed by an arterial waveform contour analysis monitor. Participants, outcome assessors, clinicians outside operating theatres and analysts were blinded to treatment allocation. Feasibility was evaluated based on: consent rate; recruitment rate; structured feedback from anaesthesia providers; and between‐group differences in blood pressure, processes‐of‐care and outcomes. The consent rate among eligible patients was 33%, with 30 participants randomly allocated to the protocol and 30 to usual care. Anaesthesia providers rated the protocol to be feasible and acceptable. The protocol was associated with reduced fluid balance and hypotension exposure in the peri‐operative setting. Postoperative complications included: acute myocardial injury in 18 (30%); acute kidney injury in 17 (28%); and surgical site infection in 7 (12%). The severity of complications was rated as moderate or severe in 25 (42%) participants. In summary, this single‐centre study confirmed the feasibility of a multicentre trial to assess the efficacy and safety of a physiologically guided treatment protocol for intra‐operative hypotension based on minimally invasive haemodynamic monitors.